Radiofrequency for Chronic Knee Pain: A Literature Review - Shang C; Sun N; Lv Z; Yin D; Feng C (Journal of Pain Research)
Chao Shang, Ning Sun, Zixu Lv, Donghua Yin, Chunlin Feng Department of Pain Management, Zibo First Hospital, Zibo, Shandong, People’s Republic of ChinaCorrespondence: Chunlin Feng, Department of Pain Management, Zibo First Hospital, No. 4 Emeishan East Road, Boshan District, Zibo, Shandong, People’s Republic of China, Tel +86-185-5337-2976, Fax +86-534-4252450, Email fengchunlin1234@126.comObjective: This review aimed to explore the current applications of radiofrequency (RF) therapy in managing chronic knee pain and to compare different treatment strategies.Methods: A comprehensive review of recent literature was conducted, concentrating on variations in target selection, guidance techniques, and treatment parameters that influence therapeutic outcomes.Results: RF therapy is a minimally invasive and effective treatment for chronic knee pain, providing faster recovery compared with traditional interventions. However, differences in treatment options can lead to significant variability in the efficacy and safety.Conclusion: A thorough understanding of the distinct characteristics of various RF therapy strategies is required for optimizing chronic knee pain management. Future research should emphasize systematic evaluation of these approaches to refine clinical practice and establish evidence-based pain management protocols.Keywords: radiofrequency, chronic knee pain, pain management, treatment strategies